Tingkat Mortalitas Ikan Mas Hidup Hasil Penyimpanan Sistem Kering Di Kabupaten Minahasa Utara Yang Didistribusikan Ke Luar Kabupaten, Kota Dan Pulau Di Sulawesi Utara - Pongoh, Jenki; Suwetja, I Gede Prabawa (Journal of Marine and Aquatic Sciences; Vol 5 No 2 (2019), 2019)
Calculation of mortality rates of lives carp fish after stored in dry sitem at North Minahasa prefecture that distributed to another prefecture, town and island was done. Mortality rates was calculated after fainting, holding in rice husk media, and recovery. Fainting technic was applicated in 8oC.Packing in rice husk media with temperature of 10-15oC. Then, recovery was done in water temperature of 25-27oC, and aerated with 3 volt aerator. And then, calculation of mortality rates was done in the distribution location. Distribution location were to another prefecture and town, that were Minahasa Selatan Prefecture with Amurang town, Minahasa prefecture with Tondano town, and Bunaken island. The average of mortality rates of lives carp fish in Bunaken island was 33.5%, lower than that in Tondano town with average of mortality rates was 45.8%, and in Amurang town with average of mortality rates was  41%.